2009
DOI: 10.1097/mog.0b013e328331b62a
|View full text |Cite
|
Sign up to set email alerts
|

Gastric exocrine and endocrine secretion

Abstract: Despite our vast knowledge, the understanding of the regulation of gastric acid secretion in health and disease is far from complete. A better understanding of the pathways and mechanisms regulating acid secretion should lead to improved management of patients with acid-induced disorders as well as those who secrete too little acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 53 publications
1
32
1
2
Order By: Relevance
“…Another important feature is that the degree of indirect or direct mediation of histamine by gastrin is not altered during ACh stimulation, suggesting that under our experimental conditions ACh may have no effect on the G cell. This is different from other studies on various species where gastrin levels have been shown to be elevated or inhibited by cholingeric agents (13,34).…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Another important feature is that the degree of indirect or direct mediation of histamine by gastrin is not altered during ACh stimulation, suggesting that under our experimental conditions ACh may have no effect on the G cell. This is different from other studies on various species where gastrin levels have been shown to be elevated or inhibited by cholingeric agents (13,34).…”
Section: Discussioncontrasting
confidence: 50%
“…In A, gastrin predominately stimulates gastric acid secretion by activating the cholecysokinin-2 (CCK2) receptors on the parietal cell rather than via the ECL cell. However, it is currently believed that gastrin stimulates the ECL cell to release histamine (34,35). When decomposing the total output of the parietal cell, gastrin plays a more significant role on gastric acid release than histamine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main functions of ghrelin are stimulation of growth hormone secretion and regulation of energy balance. In addition, loss of weight caused by lowmedium caloric diet, exercise, anorexia nervosa, organ (heart, lung, kidney and liver) failure, or malignant tumor cachexia could lead to increased level of ghrelin [10,11]. It has been indicated that in addition to being a short-term signal for eating regulation, ghrelin is also a long-term signal for nutritional status.…”
Section: Introductionmentioning
confidence: 99%